Twenty-six characters : an alphabetical book about Nokia Pure - Nokia Design (Berlin : Gestalten, 2011)
This exploration of Nokia's new typeface offers inspiration and insight for establishing an indispensable visual language. There are 26 letters in the Latin alphabet. More than merely letters, they are also characters, each possessing unique traits and qualities. And character is what makes a typeface great. Twenty-six characters details how Nokia's new typeface, Nokia Pure, was designed and developed with the user interface in mind and how it was crafted into a contemporary font. Twenty-six characters is also design inspiration, a specimen sheet, a rough guide to typography, and the tale of a global business undergoing radical change. All in all, it's a visual treat for type lovers and experts--and the first step in establishing a visual language.
boek